In vitro evaluation of osteoblast responses to carbon nanotube-coated titanium surfaces - K. Subramani; S. N. Pandruvada; D. A. Puleo; J. K. Hartsfield; S. S. Huja (SpringerOpen, 2016)
Abstract Background The effects of surface roughness and carboxyl functionalization of multi-walled carbon nanotubes (MWCNTs) mixed with collagen coated onto titanium (Ti) substrates on MC3T3-E1 osteoblasts were evaluated. Methods The proliferation, differentiation, and matrix mineralization were investigated using (1) smooth-surfaced Ti discs, (2) Ti discs coated with collagen and MWCNT (Ti-MWCNT), and (3) Ti discs coated with collagen and MWCNT-COOH (Ti-MWCNT-COOH) for applications in orthodontic mini screw implants (MSIs). The coatings were uniform when analyzed using scanning electron microscopy (SEM), and surface roughness was evaluated by surface profilometry that demonstrated similar surface roughness (R a , mean ± SD) in the MWCNT (0.83 ± 0.02 μm) and MWCNT-COOH (0.84 ± 0.01 μm) groups. MTT (3-(4,5-dimethylthiazol-2-Yl)-2,5-diphenyltetrazolium bromide) assay was performed after days 1, 3, and 7 to assess proliferation. Alkaline phosphatase (ALP)-specific activity was assessed after day 7 to quantify differentiation. Alizarin red staining was measured after day 28 to quantify matrix mineralization. All data were analyzed with JMP Pro11 software (SAS, USA) with a statistical significance of p  < 0.05. Results Surface profilometry demonstrated similar surface roughness (R a , mean ± SD) in the MWCNT (0.83 ± 0.02 μm) and MWCNT-COOH (0.84 ± 0.01 μm) groups. On day 7, ALP assay showed that MWCNT-COOH (mean ± SD 0.98 ± 0.26 U/μg of protein) enhanced cell differentiation when compared to the uncoated group (p = 0.05). Alizarin red staining after 28 days of cell culture revealed that MWCNT-COOH (mean ± SD 1.5 ± 0.2 OD405) increased (p = 0.03) matrix mineralization when compared to the uncoated group (0.9 ± 0.09 OD405). Conclusions This study showed that coatings containing MWCNT-COOH (increased hydrophilic surface chemistry) influence osteoblast proliferation, differentiation, and matrix mineralization and should be further studied for applications in orthodontic MSIs.